2015
DOI: 10.1097/prs.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Biomaterials

Abstract: The authors present a review of biomaterials, substances traditionally derived from human or animal tissue or, more recently, biodegradable synthetics modeled after naturally occurring resources. These constructs differ from purely synthetic materials in that they are degraded or incorporated into a host's tissue. These biomaterials include a diverse array of medical products, such as acellular dermal matrix, bone substitutes, and injectables. In this review, the authors examine various clinical applications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…AlloDerm Human tissue It has been applied in the re-construction of breast tissues, burn wounds [8].…”
Section: Market Name Origin Usefulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…AlloDerm Human tissue It has been applied in the re-construction of breast tissues, burn wounds [8].…”
Section: Market Name Origin Usefulnessmentioning
confidence: 99%
“…It has been applied in the re-construction of breast tissues [8] DermaMatrix Human tissue It has been used in the reconstruction of breast tissues and abdominal wall [8] FlexHD Human tissue It has been used in the reconstruction of breast tissues and abdominal wall [8] AlloMax Human tissue It has been used in the reconstruction of breast tissues hernia repair [8] Culled from [7] FlexHD FlexHD is an acellular hydrated dermis originated from cadaveric human allograft skin. Orenstein and colleagues in their study, compared the inflammatory response between FlexHD and Alloderm and concluded that there was a high inflammatory response for FlexHD compared to Alloderm [32] [38] mediate expander breast reconstruction using Alloderm or Der-maMatrix showed that there exist a comparable overall complication rate of 4 % [34].…”
Section: Strattice Pig Tissuementioning
confidence: 99%
“…The terms biomaterials, biologic scaffolds, bioprosthetics, and biologic matrices are used interchangeably and represent a diverse continuum of engineered products that serve as scaffolds which interact with native tissue, promoting vascular and cytologic ingrowth, cell propagation, migration, and differentiation. 1,2 Given the enormous breadth of this topic, we will focus on the use of a specific subset of biomaterials known as acellular dermal matrices (ADMs). These are materials comprised of nonliving dermal components from an allogenic (human cadaveric) or xenogenic (animal) donor.…”
mentioning
confidence: 99%
“…From this rationale, the technique offers near unlimited materials compatibility within a precise, easy-to-apply, and upscalable process. applications of enzymes in materials science, like the synthesis of polymers and the production of biopolymers from natural sources [4][5][6]. The ability of enzymes to build specific structures has however not yet been largely investigated although immense potential can be found here.…”
mentioning
confidence: 99%